2020
DOI: 10.3390/cells9020387
|View full text |Cite
|
Sign up to set email alerts
|

Separated Siamese Twins: Intronic Small Nucleolar RNAs and Matched Host Genes May be Altered in Conjunction or Separately in Multiple Cancer Types

Abstract: Small nucleolar RNAs (snoRNAs) are non-coding RNAs involved in RNA modification and processing. Approximately half of the so far identified snoRNA genes map within the intronic regions of host genes, and their expression, as well as the expression of their host genes, is dependent on transcript splicing and maturation. Growing evidence indicates that mutations and/or deregulations that affect snoRNAs, as well as host genes, play a significant role in oncogenesis. Among the possible factors underlying snoRNA/ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…To identify the regulatory factors that play a role in the development of EC, we analyzed the differential expression of genes in EC tissues using the human Genome Map TCGA database, and found that the expression levels of SNORD104 and its host gene SNHG25 were signi cantly increased in EC tissues. The expression levels of few snoRNAs correlate with that of their host genes [25] ; whereas, the expression and biological functions of most snoRNAs seem to be independent of their host genes [26,27] . In this work, we determined that SNORD104, rather than its host gene, SNHG25, promotes EC.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the regulatory factors that play a role in the development of EC, we analyzed the differential expression of genes in EC tissues using the human Genome Map TCGA database, and found that the expression levels of SNORD104 and its host gene SNHG25 were signi cantly increased in EC tissues. The expression levels of few snoRNAs correlate with that of their host genes [25] ; whereas, the expression and biological functions of most snoRNAs seem to be independent of their host genes [26,27] . In this work, we determined that SNORD104, rather than its host gene, SNHG25, promotes EC.…”
Section: Discussionmentioning
confidence: 99%
“…Some box C/D snoRNAs exhibit deregulated expression in cancer, having tumour-suppressive or oncogenic functions ( Fig. 2 ), and many are associated with major cancer hallmarks, such as sustained proliferative signalling, inhibition of cell death, and activation of invasion and metastasis in haematological malignancies and solid tumours [ 65 , 66 ]. Subsequently, the biomarker potential and functional role of snoRNA in tumorigenesis have been investigated in several malignancies.…”
Section: Cancer Associated Alterations Of Snorna Expressionmentioning
confidence: 99%
“…The majority of human snoRNAs are produced from mRNA introns or lncRNAs. Several studies have observed that the expression of snoRNAs released from spliced introns does not always correlate with the mRNA level of the host gene (44)(45)(46). A large proportion of the host genes from which snoRNAs are transcribed code for mRNAs or lncRNAs that are non-functional and are destined to be degraded by the nonsense-mediated RNA decay pathway (44).…”
Section: Snorna Identificationmentioning
confidence: 99%